(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency, type of urethral injury, the outcome of patients, and rate of complications in our setting. Study Design: A cross-sectional study Place and Duration of Study: This study was conducted at the conducted at the Urology Department, SMBB Medical University Larkana, Pakistan for 2 years from July 2018-July 2020. Materials and Methods: A total of 40 consecutive patients were enrolled in the study. Sociodemographic profile, type of injury patterns, causes of injury, management, and outcome were recorded for study participants and also examined the complication rate. Results: There were a total of forty patients. Common causes of urethral injuries were: pelvic fractures, iatrogenic injuries, penetrating injuries, among others. 18 out of forty (45%) patients experienced complications. The most common complication was stricture formation in 8 (44.4%), followed by extravasation or voiding difficulties in 3 (16.6%) patients, impotence, and painful ejaculation was observed in 2 (11.1%) patients, each. Conclusion: Urethral injuries were more common in male patients. The most common cause of injury was iatrogenic, followed by blunt/crushing trauma. Education modules on urological anatomy and catheter safety along with a thorough physical examination can aid in the prompt diagnosis and prevention of such injuries.